An overview of energy intensity of drinking water production and wastewater treatment - Spiru Paraschiv; Lizica Simona Paraschiv; Alexandru Serban (Energy Reports, 2023)
Drinking water has long been a free resource, but its cost is rising due to increased pollution of both surface and aquifer water sources. Drinking water requires special treatment to be potable and usable by the general public, treatments that consume a certain amount of energy. In addition, the treatment process of wastewater before it is discharged into the environment consumes energy. According to the study, the energy required for wastewater treatment is significantly greater than the energy required for preparing drinking water. Water treatment is a significant source of GHG emissions due to the use of energy and chemicals, and reducing energy consumption would significantly reduce our overall carbon footprint. Furthermore, the UN’s Sustainable Development Goals encourage access to safe drinking water and sanitation while also calling for greater resource efficiency. This research aims to provide an overview of the energy used in water treatment. This study attempts to depict the energy used in water treatment. Electricity consumption for water supply and wastewater treatment is substantial and has a significant environmental impact, particularly in countries where electricity is generated using fossil fuels.